The Influence of Infrastructure Management and Teacher Performance on School Quality - Wiwin Fitriani; Rohana Rohana; Neta Dian Lestari (Journal of Social Work and Science Education, 2026)
This study aims to analyze the influence of infrastructure management and teacher performance on school quality in State Junior High Schools within Tebing Tinggi District, examining both partial and simultaneous effects. Employing a quantitative ex post facto method, data were collected via questionnaires and documentation from a sample of 134 teachers and analyzed using SPSS. The results confirm that both infrastructure management and teacher performance individually have a significant positive influence on school quality. Critically, their combined effect demonstrates a statistically stronger, synergistic impact. The novelty of this research lies in its integrated investigation of tangible resource management and human resource effectiveness within a specific district context, highlighting their interdependence as pillars of institutional quality. A key practical implication is that school administrators and district policymakers must adopt holistic improvement strategies that concurrently optimize facility utilization and support teacher development initiatives. This study contributes to educational management theory by providing empirical evidence that sustainable school quality is best achieved through a dual-focused approach, effectively bridging operational management with pedagogical excellence.